Thomas kuhn’s stucture of scientic revolution and social sciences - Rajaratnam, M. (University of Jaffna, 2012)
Thomas Samuel Kuhn (1922-1996) made a remarkable revolutionary impact on the methodology of science and social sciences through his writing on the structure of scientific revolution [1962]. In this magnum opus he made a paradigm shift and a cognitive revolution in the normal sciences and the social sciences. The so-called professional research on sciences and social sciences undergone a stereotype stagnation and Thomas Kuhn gets his idea of revolutionary science through history of science to overcome this problem. This study also analyzes Thomas Kuhn’s analogy between scientific revolution and the political revolution in order to explore the common basis new philosophical methodology of sciences and social sciences and critically evaluate Thomas Kuhn’s notion of scientific revolution and the identification of anomaly or crisis in natural sciences and social sciences. In this study the original writings of Thomas Kuhn were critically analyzed with the special reference to the structure of scientific revolution. Qualitative critical hermeneutic method is being used to explore creative critical method of Thomas Kuhn in sciences and social sciences. According to Thomas Kuhn a scientific community cannot practice its profession without some sets of received beliefs, and the nature of rigorous preparation exert a deep hold on the student’s mind and normal science often suppresses the fundamental novelties and for him the normal science functions like puzzle solving. Thomas Kuhn argues that the research in the field of science education is an attempt to force nature into the conceptual boxes supplied by the professional education. According to Thomas Kuhn revolution will make a change in the world view, when the paradigm change, the world view itself changes in an extensive manner. Revolution will make a progressive impact not only in natural sciences but also in the social and political sciences and history. Such revolutionary science and successive stages in these developmental processes should be marked by an active articulation in the new fields of sciences and social sciences.
Keywords: Natural sciences; Paradigm shift; Scientific revolution; Social sciences